Analisis Perbandingan Nilai Ujian Rapot di SD Bahagia Masa dan Paska Covid-19 Menggunakan Algoritma Pemrograman - May Sharah Athifah; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research discusses a comparative analysis of school exam scores during and after the Covid-19 pandemic that were achieved by students, which was carried out at SD Bahagia. The aim of this research is to compare student learning outcomes during the Covid-19 pandemic and after the Covid-19 pandemic, to find out the process results achieved by students with online learning / learning from home and face-to-face / new normal learning. This research uses a design method to make it easier for researchers to design student data analysis with structure and steps. The results and discussion of the student report card assessments during and after the Covid-19 pandemic were very good and the average score was not below 62, so the results obtained by the students in the statement were declared passed because the students were able to follow the online learning process and understand the material provided by the teacher. , even during the Covid-19 pandemic which limits long distances. Meanwhile, after the Covid-19 pandemic, teacher and student communication was achieved which resulted in students understanding the material easily without any obstacles.